Efektivitas Permainan Lompat Geo Terhadap Kemampuan Motorik Kasar Anak Di Taman Kanak-Kanak Nur Ilaahi Padang - Ria Sulfia; Syahrul Ismet (Jurnal Family Education, 2022)
gross motor skills of children at the Nur Ilaahi Padang Kindergarten. By carrying out geo jumping game activities, It is hoped that it will be effective in order to improve gross motor skills in children. In this study the reseacher used a quantitative research type namely quasy experimental The research population is all children in Nur Ilaahi Padang Kindergarten, where the total number of children is 66 children. The sample taken for the experimental class is class B2 and the sample taken for the control class is class B3, where each class consists 15 children using cluster sampling research techniques, while the data collection technique uses an action tests, then the data is processed by a t-test, where previously the normality test and homogeneity test were carried out first and also the N-Gain score test was carried out. Based on the analysis of research data that has been carried out by researchers, then from the data obtained conclusions, namely the results of the study which showed the average value of the experimental class was 7,47 and that of the control class was 4,00.